PENGARUH ESOP, COMPANY CHARACTERISTICS, CORPORATE GOVERNANCE, DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Vincent Nathaniel Lumanto; Julisar Surjadi (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study is to provide empirical evidence related to the effect of employee stock ownership programs, company characteristics, corporate governance, and audit quality on earnings management. Company characteristics consists of information asymmetry, leverage, profitability, firm size, and firm age. Corporate governance consists of managerial ownership, institutional ownership, and audit committee. The sample of this study was selected based on the purposive sampling method and resulted in 112 non-financial companies listed on the Indonesia Stock Exchange during 2017-2019. A total of 336 data obtained were analyzed by the multiple regression method. The results of this study shown that employee stock ownership programs and audit committees have an influence on earnings management. Other variables, for examples, information asymmetry, leverage, profitability, firm size, managerial ownership, institutional ownership, audit quality, and firm age have no effect on earnings management.